Jurisdictional Immunities of the State and Exequatur of Foreign Judgments: a private International Law Evaluation of the Recent ICJ Judgment in Germany v. Italy (Stato, Chiese e pluralismo confessionale, 2012)
The article, accepted by the Director, is forthcoming in N. Boschiero, T. Scovazzi, C. Ragni, C. Pitea (eds), International Courts and the Development of International Law, Essays In Honour of Tullio Treves, T.M.C. ASSER PRESS, The Hague, The Netherlands, 2013.SUMMARY: - 1. Introduction - 1.1. Historical and factual background of the ICJ’s decision in relation to proceedings involving Greek nationals - 2. The arguments of the Court on the private international law issue of jurisdictional immunity in exequatur proceedings - 2.1. Evaluation of the Court’s reasoning: its correctness and weakness in the light of the preliminary unconvincing solution given in respect to the violation of Germany’s jurisdictional immunity in proceedings brought before the Italian courts by Italian claimants - 2.2. The external private international law context of the ICJ’s judgment: the ECJ’s Lechouritou judgment - 2.3. The problematic role of secondary European legislation (in the field of judicial cooperation in civil matters) on human rights claims against a State - 3. The negative impact of the ICJ’s decision on the role of the national/international public order exception; critical assessment of the formalistic “procedure/substance” distinction with regard to criminal and civil proceedings - 3.1 The consequences for the fundamental individual right to have access to justice and the right to an effective remedy - 4. Conclusion.